Asymptotic equivalence of discretely observed geometric Brownian motion to a Gaussian shift - Cristina Butucea; Michael Nussbaum (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
Financial models consider often stochastic processes satisfying certain differential equations. We show that the solution of a particular geometric Brownian motion observed in discrete time is asymptotically equivalent with a Gaussian white noise model.
urn:nbn:de:kobv:11-10046497
Keywords: 330